Weighted Composition Operators between the Bloch Type Space and the Hardy Space on the Unit Ball of Complex Banach Spaces. (29th September 2022) - Liu, Xiaoman; Liu, Yongmin
Abstract: Let X be a finite or infinite dimensional complex Banach space. We characterize the bounded weighted composition operators between the Bloch type space and the Hardy space on the unit ball of X, extending several known results for finite dimensional domains.